Role of Purine Nucleoside Phosphorylase in Interactions between 2′,3′-Dideoxyinosine and Allopurinol, Ganciclovir, or Tenofovir - Ray, Adrian S. (American Society for Microbiology, 2004)
The level of systemic exposure to 2′,3′-dideoxyinosine (ddI) is increased 40 to 300% when it is coadministered with allopurinol (Allo), ganciclovir (GCV), or tenofovir. However, the mechanism for these drug interactions remains undefined. A metabolic route for ddI clearance is its breakdown by purine nucleoside phosphorylase (PNP). Consistent with previous reports, enzymatic inhibition assays showed that acyclic nucleotide analogs can inhibit the phosphorolysis of inosine. It was further established that the mono- and diphosphate forms of tenofovir were inhibitors of PNP-dependent degradation of ddI (K(i)s, 38 nM and 1.3 μM, respectively). Allo and its metabolites were found to be relatively weak inhibitors of PNP (K(i)s, >100 μM). Coadministration of tenofovir, GCV, or Allo decreased the amounts of intracellular ddI breakdown products in CEM cells, while they increased the ddI concentrations (twofold increase with each drug at approximately 20 μM). While inhibition of the physiological function of PNP is unlikely due to the ubiquitous presence of high levels of enzymatic activity, phosphorylated metabolites of GCV and tenofovir may cause the increased level of exposure to ddI by direct inhibition of its phosphorolysis by PNP. The discrepancy between the cellular activity of Allo and the weak enzyme inhibition by Allo and its metabolites may be explained by an indirect mechanism of PNP inhibition. This mechanism may be facilitated by the unfavorable equilibrium of PNP and the buildup of one of its products (hypoxanthine) through the inhibition of xanthine oxidase by Allo. These findings support the inhibition of PNP-dependent ddI degradation as the molecular mechanism of these drug interactions.